2000
DOI: 10.1016/s0035-9203(00)90103-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a mass community effect of insecticide-treated bednets on the incidence of malaria on the Kenyan coast

Abstract: The use of insecticide-treated bednets (ITBNs) has been shown to be effective in reducing mortality and morbidity from malaria. However, there is mixed evidence as to whether or not community-wide use of ITBNs engenders a 'mass effect', such that those not sleeping under bednets are offered protection from widespread ITBN use in the area in which they live. We have analysed data collected in Kilifi, Kenya, from a cohort of children followed from birth to investigate how the degree of net usage in the locality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
123
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 13 publications
11
123
0
1
Order By: Relevance
“…Proper ITN users provide the community effect which indirectly protects all players from malaria [9,7,10]. By free riding on the community effect, each improper ITN user can decrease its infection probability without abandoning extra income from ITN misuse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proper ITN users provide the community effect which indirectly protects all players from malaria [9,7,10]. By free riding on the community effect, each improper ITN user can decrease its infection probability without abandoning extra income from ITN misuse.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the community effect decreases every player's infection probability regardless of strategy. Properly-used ITNs repel or kill mosquitoes when they approach or contact the nets, likely reducing the entomological risk of malaria infection [9,7,10]. We assume that when m-players, m ∈ {0, 1, .…”
Section: Structure Of the Gamementioning
confidence: 99%
See 1 more Smart Citation
“…the proportion of houses in a given area with ITNs Gimnig et al, 2003). Eighth, evidence for the existence of a community-wide effect due to marked reduction in vector populations (Howard et al, 2000;Hii et al, 2001;Maxwell et al, 2002), implying that ITNs have substantial effects at the population level. Finally, all these public health benefits of ITNs were sustained for up to 6 years and there is no evidence that bed-net use from birth increases all-cause mortality in older children (Lindblade et al 2004).…”
Section: Benefit Of Itns Usementioning
confidence: 99%
“…Experimental surveys have confirmed efficacy of these methods in terms of reduction of incidence of malarial disease (Carnevale et al 1991;Lengeler 1998), and overall infant mortality in Ghana (Binka et al 1996), Kenya (Nevill et al 1996), Burkina Faso (Habluetzel et al 1997) and The Gambia (D'Alessandro et al 1995). Moreover, recent trials showed a mass effect of permethrin-impregnated nets in Ghana (Binka, Indome and Smith 1998), in Kenya (Howard et al 2000) and with impregnated curtains in Burkina Faso (Diallo et al 2004) with no rebound mortality even after several years of ITN usage (Binka et al 2002;Hawley et al 2003;Maxwell et al 2003). It was noticed that when some coverage of the population (60 to 80%) was maintained, even people not covered by ITNs can be protected from malaria if they are living inside 'treated' compounds or in their vicinity (less than 300m).…”
Section: Vector Controlmentioning
confidence: 93%